Prinsip Kepastian Hukum Akta Pendirian Perseroan Terbatas Bidang Usaha Perjudian Dan Pertaruhan - Nur Aisya hidayati; Aries Harianto; Herowati Poesoko (Jurnal Syntax Transformation, 2022)
The problems and research objectives taken include reviewing and analyzing the meaning of gambling and betting carried out by a Limited Liability Company as a line of business that is contrary to the concept of a Limited Liability Company established by an agreement, reviewing and analyzing the classification arrangement of gambling and betting related to the Limited Liability Company's line of business. Contradicts the principle of legal certainty and examines and analyzes the principle of legal certainty as a guideline for future arrangements for the establishment of a Limited Liability Company that runs the gambling and betting business.The research method used is legal research. The problem approach used in this research is the statute approach, the conceptual approach and the case approach. The sources of legal materials used are primary and secondary legal materials. The results of the study conclude First, that the use of the gambling and betting business sector by the Limited Liability Company is based on the obligation to include business activities in the deed of establishment in the article of intent and purpose. However, the meaning of gambling which means a game of chance by risking a certain amount of money whose outcome is not certain is contrary to the objective requirements in Article 1320 of the Civil Code which is the basis for the establishment of a Limited Liability Company established under an agreement. Second, the regulation of the gambling and betting business sector in Article 303 bis of the Civil Code and Central Statistics Agency Regulation No. 2 of 2020 concerning the Standard Classification of Indonesian Business Fields (KBLI) is contrary to the principle of legal certainty because it does not pay attention to the special provisions governing gambling and betting, namely Law no. 7 of 1974 jo. Government Regulation No. 9 of 1984 concerning Gambling Control and does not reflect the values ​​of Pancasila and the 1945 Constitution. Third, future arrangements for the gambling and betting business sector must pay attention to 3 (three) legal objectives, namely justice, benefit and legal certainty by eliminating the gambling business sector. and betting in the KBLI and there must be regulation on the determination of the existing business fields in the KBLI.